1998
DOI: 10.1016/s0954-6111(98)90213-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of chlorofluorocarbon-free beclomethasone dipropionate 400 μg day−1 delivered as an extrafine aerosol in adults with moderate asthma

Abstract: Beclomethasone dipropionate (BDP) has been reformulated in a chlorofluorocarbon-free propellant, hydrofluoroalkane-134a (HFA), resulting in an extrafine aerosol which gives improved drug delivery to the airways. The objective of this 6 week, placebo-controlled study was to evaluate the clinical efficacy of HFA-BDP 400 micrograms day-1 in 256 adult patients with moderate asthma. This is a lower daily dose than that recommended for existing BDP inhalers in current treatment guidelines for moderate asthma (NIH pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…bo-controlled studies (e.g., in the discussion section of the publication, in 3 trials) (Guay et al, 1999;Guez et al, 1996;Saekeland and Albrecht, 1997), or included an additional placebo or 'minor control' (a treatment assumed to be inferior compared to the standard included in the actual trial) group (Aubier et al, 1999;Day et al, 2000;DuBiner et al, 1996;Dulin et al, 1998;Elfstraem et al, 1999;Farnier, Portal and Maigret, 2000;Lallemant et al, 2000;Matthys et al, 1998;Rehn et al, 1996;Sall, 2000;Singer et al, 2000). Here the median of the 'preserved' effect referred to the point estimate amounts to about 15% (data not shown), including four trials in which the irrelevance margin was even larger than that point estimate.…”
Section: Resultsmentioning
confidence: 99%
“…bo-controlled studies (e.g., in the discussion section of the publication, in 3 trials) (Guay et al, 1999;Guez et al, 1996;Saekeland and Albrecht, 1997), or included an additional placebo or 'minor control' (a treatment assumed to be inferior compared to the standard included in the actual trial) group (Aubier et al, 1999;Day et al, 2000;DuBiner et al, 1996;Dulin et al, 1998;Elfstraem et al, 1999;Farnier, Portal and Maigret, 2000;Lallemant et al, 2000;Matthys et al, 1998;Rehn et al, 1996;Sall, 2000;Singer et al, 2000). Here the median of the 'preserved' effect referred to the point estimate amounts to about 15% (data not shown), including four trials in which the irrelevance margin was even larger than that point estimate.…”
Section: Resultsmentioning
confidence: 99%
“…A placebo‐control design was not chosen for the study, since it was considered unethical for an asthmatic patient dependent on inhaled steroids to receive a placebo. Double‐blind studies have, however, previously demonstrated the efficacy of HFA‐BDP compared with placebo 16,17 …”
Section: Discussionmentioning
confidence: 99%
“…2 -4 Scintigraphic studies, in healthy volunteers as well as in patients with asthma, have shown HFA-BDP to have better deposition in the lungs and less deposition in the oropharynx, compared with CFC-BDP. 5,6 Subsequent studies have demonstrated the clinical efficacy of HFA-BDP versus placebo in steroid-naïve patients, 7,8 and in comparison with already existing substances and formulations. For example, half of the dose of HFA-BDP was as equally effective as conventional CFC-BDP 9 -12 and budesonide turbuhaler (BUD-TH), 13,14 whereas a dose equivalence was shown when compared with CFC-fluticasone.…”
Section: Introductionmentioning
confidence: 99%